Structural Studies of Robert Stanton in The Folklore of Luwu (Worongporong dan Pariama) - Nurul Khairani Abduh; Masruddin Masruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to describe the intrinsic elements in the folklore of Luwu Worongporong and Pariama using the study of Robert Stanton's structural theory. The data generated is descriptive data that is written in the form of words, expressions, and sentences. There are two sources of data used, namely primary and secondary data. The data collection technique used is reading and note-taking technique. The results of this study describe the themes in the folklore of Worongporong and Pariama which are divided into major and minor themes. There are facts of the story which are divided into three parts, namely plot, character and setting, as well as literary means that describe the point of view and style of language.